PET hypermetabolism in medically resistant childhood epilepsy: Incidence, associations, and surgical outcome. (18th January 2016) - Bansal, Lalit; Miller, Ian; Hyslop, Ann; Bhatia, Sanjiv; Duchowny, Michael; Jayakar, Prasanna
Summary: Objective: We observed several children with medically resistant epilepsy demonstrating focal positron emission tomography (PET) hypermetabolism, a finding rarely reported and of questionable significance. We therefore retrospectively reviewed the incidence of hypermetabolic PET, and its relationship to electroencephalography (EEG) and magnetic resonance imaging (MRI) findings, and to the outcome of epilepsy surgery. Methods: We retrospectively reviewed 498 PET brain studies in patients with medically resistant childhood epilepsy for evidence of hypermetabolism. In patients with PET hypermetabolism, we correlated metabolic abnormality with the scalp EEG and MRI findings. In a subset of patients who underwent surgical resection, we further correlated the PET findings with histopathologic and surgical outcomes. Results: Focal PET hypermetabolism was identified in 33 (6.6%) of 498 studies. The region of hypermetabolism correlated with a spike count of ≥10 per minute in 26 of 32 concomitant scalp EEG studies and 18 of 21 lesions evident on MRI. In 17 patients who underwent surgical resection, PET hypermetabolism further correlated with regions revealing almost continuous epileptiform discharges on the intracranial EEG and with histopathologically malformative tissue. At a minimum follow‐up of 1 year postsurgery (median 33 months), 7 (50%) of 14 patients had Engel's class I outcome, 4 patients had class II, and 2 had class III outcome, whereas one patient was unchanged. At last follow‐up, seizure freedom was noted in five of seven patients with focal PET hypermetabolism alone versus three of eight patients with PET hypometabolism. Significance: Focal PET hypermetabolism is associated with high spike frequency on scalp EEG and can occur in the absence of ictal events during the peri‐injection period. Correlation with intracranial EEG usually corroborates the highly epileptogenic pathophysiologic state. Cortical malformations constitute the most common pathologic substrate, and resection of the hypermetabolic PET region may facilitate favorable outcomes. These observations indicate that focal PET hypermetabolism is an important marker of the epileptogenic zone and may represent its epicenter.